The Effect of Work Stress and Conflict on Employee Performance at PD. Bumi Wiralodra Indramayu - Meddy Nurpratama; Agus Yudianto (Jurnal EMT KITA, 2022)
Currently, more and more companies, both government and private, realize that the influence of work stress and conflict is very large to produce productive employee performance, so that the role of work stress in carrying out their duties, authorities and responsibilities as well as the influence of conflict between leaders and their subordinates can stimulate subordinates in carrying out their duties. and responsibilities so as to achieve the expected company goals in a productive and efficient manner. This research was conducted to find out how the level of work stress, conflict and employee performance levels were carried out at PD. Bumi Wiralodra Indramayu, and how much influence work stress and conflict have on the performance of PD employees. Earth Wiralodra Indramayu. The method used in this research is descriptive and verification method. The types of data needed for research are primary data and secondary data, while the techniques used in collecting data for research are interviews, questionnaires and literature study. The sample taken is 38 respondents. Data processing and analysis was carried out quantitatively using statistical methods, namely to find out how much influence work stress and conflict had on the performance of PD employees. Bumi Wiralodra Indramayu uses path analysis. The results showed the level of work stress in PD. Bumi Wiralodra Indramayu, is in the very high category. This shows that 23 respondents from 38 respondents (60.53%) stated that they strongly agreed with the work stress carried out by PD. Bumi Wiralodra Indramayu, the level of conflict in PD. Bumi Wiralodra Indramayu, is in the very high category. This shows that 28 respondents out of 38 respondents (73.68%) stated that they strongly agree with the conflict carried out in PD. Bumi Wiralodra Indramayu and the level of employee performance variables PD. Bumi Wiralodra Indramayu, is in the medium and high category. This shows that 13 respondents out of 38 respondents (34.21%) expressed doubt and agreed with the performance carried out in PD. Bumi Wiralodra Indramayu, although there are still some who have not fully delivered and implemented this performance well, this can be seen from the level of performance variables which show medium and high levels. From the path analysis results, the structural function equations are obtained, as follows: Y = -0.364 X1 + 0.299 X2. Based on these calculations, it can be stated that work stress (X1) affects changes in employee performance (Y) by 13.2% and conflict (X2) affects changes in employee performance (Y) by 8.9% and work stress and conflict (X1X2) affects changes in employee performance (Y) of 13.1%, and the influence of other variables outside the variables used = 0.932 (86.86%). The magnitude of the influence of other variables, which is 86.86%, indicates that there are other influences besides work stress (X1) and conflict (X2) which are very large on changes in the performance of PD employees. Bumi Wiralodra Indramayu, the value of Fcount is 2.639 < Ftable 3.27 while the value of tcount is -2.097 (X1) and 1.727 (X2) > ttable 1.689. The residual variables consist of factors that are not studied, such as; job satisfaction, organizational commitment, organizational culture, communication systems, and others.